APPLICATION OF THE SCRUM FRAMEWORK AS A PEDAGOGICAL STRATEGY FOR COLLABORATIVE MANAGEMENT - de Souza, Inarha Stefany Meith; Neves, Ester Hadassa; da Silva, Taina Kleinubing; Massarollo, Kelly Cristina; Ricardo, Letycia Lopes; de Moura, Wagner Filipe Soares (ARACÊ, 2024)
Agile methodologies can be described as a flexible management tool that can be applied in various fields, such as education. The Scrum method is an agile methodology that allows the team to work on different types of projects. Aiming to introduce agile methodologies in the educational field, this work was developed with the application of the Scrum method in a college classroom, where the students acted as the Scrum Team and the teacher as the Product Owner. The project was based on the application of agile methods to the writing of a scientific article. To this end, the students were divided into 3 teams, each of which had as its product the writing and publication of a scientific article. The inclusion of tools such as 5W2H and Trello served as allies in the development of the project, bringing a significant increase in the performance and communication of the teams, thus proving that the combination of strategies allows the teams to perform better in the delivery of the product.